CALIBRATION CHARACTERISTICS OF A TWO-CHANNEL PIEZOELECTRIC GRAVIMETER - Безвесильная, Елена; Киричук, Юрий; Назаренко, Наталья (SWorldJournal, 2021)
Construct the calibration characteristic of a two-channel piezoelectric gravimeter of an aviation gravimetric system and establish the dependence of the angle of rotation of the measuring axis of the gravimeter relative to the reference vertical.